Reassessing Child Labour Protection in Indonesia: Evaluating the Effectiveness of Law No. 35 of 2014 through a Socio-Legal Perspective - Misdin Arifin HM; Siti Nurjannah Lase; Zahara Ananda; Layla Hasfajira; Gilang Ade Prabowo (Jurnal Sahabat ISNU SU, 2026)
Child labour remains a persistent legal and human rights issue in Indonesia despite the enactment of Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 on Child Protection, which explicitly prohibits the economic exploitation of children. The continued prevalence of child labour indicates a significant gap between the normative framework and its practical implementation. This study aims to analyze the effectiveness of the implementation of Law No. 35 of 2014 in protecting children from labour exploitation, identify the principal obstacles to law enforcement, and formulate policy reforms to strengthen child labour protection in Indonesia. This research employs a normative juridical method using statutory, conceptual, comparative, and case approaches. Legal materials were analyzed through qualitative legal reasoning by examining national legislation, international labour standards, legal doctrines, and recent statistical data published by the Central Statistics Agency (BPS), the International Labour Organization (ILO), and UNICEF. The findings reveal that Indonesia possesses a relatively comprehensive legal framework aligned with international standards, including ILO Conventions No. 138 and No. 182. However, implementation remains constrained by fragmented institutional coordination, inadequate labour inspection, weak law enforcement, disparities in regional governance capacity, socio-economic inequalities, and the dominance of informal employment sectors where child labour is difficult to monitor. These challenges significantly reduce the effectiveness of legal protection despite the existence of criminal sanctions. The study concludes that strengthening child labour protection requires an integrated legal policy combining effective law enforcement, cross-sectoral institutional coordination, enhanced labour inspection systems, digital governance, social protection programs, and community participation. The proposed Integrated Child Labour Protection Framework (ICLPF) offers a comprehensive legal policy model to bridge the gap between legal norms and practical implementation while reinforcing Indonesia's commitment to protecting children's rights in accordance with national and international legal standards.